The Smart Society and Its Enemies. Meanings and Limits in the Criticism of Smartness - Susca, Emanuela (SocietàMutamentoPolitica, 2023)
Distancing myself from unreflective appropriations, in this article, I trace a brief history of smartness by dwelling mainly on the differentiation of smartness itself from intelligence, digitization or simple competitiveness to propose an idea that focuses on the integration of people, environment, and technologies. Moreover, after analyzing some not insignificant misgivings about the delimitation of places and relations, I offer some useful elements to distinguish progressive criticism, which aims at the empowerment of the majority, from merely regressive and ultimately unhelpful criticism. I conclude by pointing out that smartness, in addition to helping the social sciences, particularly sociology, frame fundamental and still unresolved issues in new ways, is now an unavoidable topic for researchers.